Larval mortality of Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) in fruits of pineapple guava (Acca sellowiana [O. Berg] Burret) during a cold quarantine treatment - VALDERRAMA, J. KATERINE; SERRANO, MIGUEL S.; FISCHER, GERHARD (Revista Colombiana de Entomología, 2005)
The South American fruit fly Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) is a quarantine pest of pineapple guava. Artificially infested fruits were subjected to cold treatment “t107a” (1.1° C for 15 d), required by USDA-APHIS for exportation and were compared to control fruits maintained at room temperature. Four third-instar larvae were infested per individual fruit in two treatments with 50 replicates. Body length, volume, behavior, mortality and color changes of the larvae were recorded daily in a sample of three fruits. The first behavioral change observed in larvae under cold quarantine treatment was an attempt to abandon the fruits. No variation in body length or volume was observed under the cold quarantine treatment. In the untreated control, larvae increased body volume up to the final molt to pupa. The cold quarantine treatment affected larval development and the larva-pupa molt. All larvae died on the eighth day of cold treatment. Most larvae died while molting to pupa and exhibited a dark coloration or “partial molt”. Under the cold quarantine treatment, damage to fruits did not exceed 24% where as in the untreated control it reached 74%. This is the first cold quarantine treatment tested for this pest of pineapple guavas in Colombia and it provided total control. Compliance with the quarantine requirements of USDA-APHIS opens the international market for Colombian exporters of pineapple guava.